Phosphorus-based composite negative electrode material, alkali metal ion battery negative electrode, and preparation method and application thereof
Patent Information
- Application Number
- CN202611189179.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-30
AI Technical Summary
然而,在电化学循环过程中,磷与碱金属离子发生合金化/脱合金化反应时通常伴随复杂的固相转变和中间相演化,存在反应动力学缓慢、体积膨胀明显、电子电导率低等问题,导致界面稳定性差、极化严重和循环寿命受限,制约了磷基负极材料的实际应用
[0010]根据本发明的实施方案,通过在磷基复合负极材料中引入碱金属快离子导体添加相,在磷主体材料中构建富碱金属离子的局域传输促进结构,降低合金化/脱合金化过程中的反应阻抗和极化程度,提高界面反应活性,从而促进磷的合金化/脱合金化反应,进而提高磷基复合负极材料的反应动力学与高倍率性能。本发明引入的碱金属快离子导体添加相在电化学循环过程中能够稳定存在,可持续促进磷基复合负极材料的反应动力学。碱金属快离子导体添加相具有较高的离子电导率及对碱金属离子的亲和特性,使其在低温(-50-0℃)条件下仍能维持较快的离子迁移速率,从而缓解低温环境中因扩散受限导致的极化加剧和容量衰减等问题,进而提高磷基复合负极材料的低温电化学性能与循环稳定性。
Smart Images

Figure CN123017924A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrochemical energy storage materials technology, and in particular to a phosphorus-based composite anode material, an alkali metal ion battery anode, its preparation method and application. Background Technology
[0002] With the accelerated transformation of the energy structure and the rapid development of electric vehicles, large-scale energy storage power stations, and other fields, higher requirements are being placed on the energy density, safety performance, rate performance, and low-temperature (-50-0℃) adaptability of secondary batteries. Lithium-ion batteries are currently the most widely used energy storage devices, and their overall electrochemical performance is highly dependent on the anode material system. The theoretical specific capacity of commercial graphite anodes is limited, making it difficult to meet the development needs of high-energy-density batteries.
[0003] Alloy-based anode materials have attracted widespread attention due to their high theoretical specific capacity. Among them, phosphorus-based anode materials possess both high theoretical specific capacity and volumetric energy density, making them promising anode materials for application. However, during electrochemical cycling, the alloying / dealloying reactions between phosphorus and alkali metal ions are usually accompanied by complex solid-phase transformations and intermediate phase evolutions. This results in problems such as slow reaction kinetics, significant volume expansion, and low electronic conductivity, leading to poor interfacial stability, severe polarization, and limited cycle life, thus restricting the practical application of phosphorus-based anode materials.
[0004] Therefore, there is an urgent need to develop a phosphorus-based anode material. Summary of the Invention
[0005] In view of this, in order to at least partially solve the aforementioned technical problems, the present invention provides a phosphorus-based composite anode material, an alkali metal ion battery anode, a preparation method thereof, and its application.
[0006] According to one embodiment of the present invention, a phosphorus-based composite anode material is provided, comprising a phosphorus host material, a carbon conductive phase, and an alkali metal fast ion conductor additive phase; the alkali metal fast ion conductor additive phase comprises at least one selected from alkali metal sulfides, alkali metal selenides, alkali metal tellurides, alkali metal nitrides, and alkali metal halides.
[0007] According to another embodiment of the present invention, a method for preparing the above-mentioned phosphorus-based composite anode material is provided, comprising: combining a phosphorus host material with an additive phase precursor to obtain a first composite material; combining the first composite material with a carbon conductive phase to obtain a second composite material; subjecting the second composite material to a pre-alkali metallization treatment with an alkali metal under a protective gas, so that the alkali metal reacts with the additive phase precursor to form an alkali metal fast ion conductor additive phase, thereby obtaining a phosphorus-based composite anode material comprising a phosphorus host material, a carbon conductive phase, and an alkali metal fast ion conductor additive phase; or combining the phosphorus host material with the alkali metal fast ion conductor additive phase and the carbon conductive phase to obtain a phosphorus-based composite anode material.
[0008] According to another embodiment of the present invention, an alkali metal ion battery anode is provided, comprising the above-mentioned phosphorus-based composite anode material, a conductive agent, a binder, and a current collector.
[0009] According to another embodiment of the present invention, the application of the above-mentioned phosphorus-based composite anode material or the above-mentioned alkali metal ion battery anode in an alkali metal secondary battery is provided.
[0010] According to an embodiment of the present invention, by introducing an alkali metal fast ion conductor additive phase into the phosphorus-based composite anode material, a local transport-promoting structure rich in alkali metal ions is constructed in the phosphorus host material. This reduces the reaction impedance and polarization degree during alloying / dealloying, improves interfacial reaction activity, and thus promotes the alloying / dealloying reaction of phosphorus, thereby enhancing the reaction kinetics and high-rate performance of the phosphorus-based composite anode material. The alkali metal fast ion conductor additive phase introduced in this invention can exist stably during electrochemical cycling, continuously promoting the reaction kinetics of the phosphorus-based composite anode material. The alkali metal fast ion conductor additive phase has high ionic conductivity and affinity for alkali metal ions, enabling it to maintain a relatively fast ion migration rate even at low temperatures (-50-0℃), thereby alleviating problems such as increased polarization and capacity decay caused by diffusion limitation in low-temperature environments, and thus improving the low-temperature electrochemical performance and cycle stability of the phosphorus-based composite anode material. Attached Figure Description
[0011] Figure 1 The image shows a scanning electron microscope (SEM) image and elemental distribution map of the first composite material in Example 1.
[0012] Figure 2 SEM image and elemental distribution diagram of the first composite material in Example 2;
[0013] Figure 3 The image shows the SEM image and elemental distribution diagram of the first composite material in Example 3.
[0014] Figure 4 SEM image and elemental distribution diagram of the first composite material in Example 4;
[0015] Figure 5 SEM image and elemental distribution diagram of the first composite material in Example 5;
[0016] Figure 6 SEM image and elemental distribution diagram of the first composite material in Example 6;
[0017] Figure 7 SEM image and elemental distribution diagram of the phosphorus-based composite anode material in Example 7;
[0018] Figure 8 Here are the SEM images and elemental distribution diagrams of the phosphorus-based composite anode material in Example 8;
[0019] Figure 9 SEM image and elemental distribution diagram of the phosphorus-based composite anode material in Example 9;
[0020] Figure 10 SEM image and elemental distribution diagram of the phosphorus-based composite anode material of Example 10;
[0021] Figure 11 SEM image and elemental distribution diagram of the phosphorus-based composite anode material of Example 11;
[0022] Figure 12 SEM image and elemental distribution diagram of the phosphorus-based composite anode material in Example 12;
[0023] Figure 13 The Se K-edge X-ray absorption near-edge structure spectrum of the phosphorus-based composite anode material and the corresponding added phase precursor and the first composite material in Example 7;
[0024] Figure 14 The charge-discharge curves of the lithium-ion coin cell half-cell used in Application Example 1 are shown.
[0025] Figure 15 The charge-discharge curves of the lithium-ion coin cell half-cell used in Application Example 2 are shown.
[0026] Figure 16 The charge-discharge curves of the lithium-ion button half-cell used in Application Example 3 are shown.
[0027] Figure 17 The charge-discharge curves of the lithium-ion coin cell in Application Example 4 are shown.
[0028] Figure 18 The charge-discharge curves of the lithium-ion coin cell half-cell used in Application Example 5 are shown.
[0029] Figure 19 The charge-discharge curves of the lithium-ion coin cell half-cell in Comparative Example 1 are shown.
[0030] Figure 20 The charge-discharge curves and state of charge (SOC)-time curves of the sodium-ion coin cell in Example 6 at different charge-discharge rates are shown.
[0031] Figure 21 The graph shows the areal capacity and coulombic efficiency of the lithium-ion coin cells in Application Example 7 and Comparative Example 1 as a function of the number of cycles at a temperature of -10°C.
[0032] Figure 22The charge-discharge curves of the lithium-ion coin cells used in Application Example 7 and Comparative Example 1 at a temperature of -20°C are shown. Detailed Implementation
[0033] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the invention. In the following detailed description, numerous specific details are set forth to provide a thorough understanding of the embodiments of the invention for ease of explanation. However, it will be apparent that one or more embodiments may be practiced without these specific details. Furthermore, descriptions of well-known structures and techniques are omitted in the following description to avoid unnecessarily obscuring the concept of the invention.
[0034] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the invention. The term "comprising" as used herein indicates the presence of features, steps, or operations, but does not exclude the presence or addition of one or more other features.
[0035] When using expressions such as "at least one of A, B and C", they should generally be interpreted in accordance with the meaning that is commonly understood by those skilled in the art (e.g., "a system having at least one of A, B and C" should include, but is not limited to, a system having A alone, a system having B alone, a system having C alone, a system having A and B, a system having A and C, a system having B and C, and / or a system having A, B and C, etc.).
[0036] Currently, methods such as carbon coating, conductive framework compositing, and structural size control are mainly used to modify phosphorus-based anode materials, which can alleviate the volume effect and improve electron transport capabilities to some extent. However, these methods mainly focus on the passive control of material structure and cannot fundamentally solve the problems of limited ion transport and sluggish interfacial reaction kinetics during the alloying reaction. In addition, it is difficult to achieve both high energy density and high power density, especially under low temperature (-50-0℃) or rapid charge-discharge conditions, making long-term stable operation difficult.
[0037] In the process of realizing this invention, it was discovered that by introducing an alkali metal fast ion conductor additive phase, a fast ion migration channel is constructed and the interfacial reaction kinetics are controlled, so as to achieve a synergistic improvement in high energy density, high power density and excellent cycling stability.
[0038] Specifically, according to one embodiment of the present invention, a phosphorus-based composite anode material is provided, comprising a phosphorus host material, a carbon conductive phase, and an alkali metal fast ion conductor additive phase; the alkali metal fast ion conductor additive phase comprises at least one of alkali metal sulfides, alkali metal selenides, alkali metal tellurides, alkali metal nitrides, and alkali metal halides.
[0039] According to embodiments of the present invention, an alkali metal fast ion conductor additive phase is introduced into a phosphorus-based composite anode material, thereby constructing a local structure in the phosphorus host material that facilitates the rapid migration of alkali metal ions. The alkali metal fast ion conductor additive phase can act as a stable ion transport promoting phase during the alloying reaction, reducing ion migration impedance, increasing interfacial reaction activity, thereby lowering the energy barrier of the phosphorus alloying reaction and promoting the breaking of PP bonds and the formation of PM bonds (M being an alkali metal) during alloying. The present invention can improve the problems of limited ion transport, sluggish interfacial reaction kinetics, and severe polarization in phosphorus-based composite anode materials, synergistically improving rapid charge-discharge capability, low-temperature (-50-0℃) electrochemical performance, and cycle stability.
[0040] In some embodiments, the alkali metal fast ion conductor additive phase is obtained by pre-alkali metallization treatment of an additive phase precursor and an alkali metal under a protective atmosphere. The additive phase precursor includes at least one of elemental sulfur, elemental selenium, elemental tellurium, elemental iodine, and elemental bromine, and the alkali metal includes lithium, sodium, or potassium. During the pre-alkali metallization treatment, elements such as sulfur, selenium, tellurium, iodine, and bromine can undergo atomic-level in-situ bonding reactions with the alkali metal to generate the alkali metal fast ion conductor additive phase. This atomic-level in-situ construction method can eliminate the aggregation defects of the alkali metal fast ion conductor additive phase, form a continuous ion transport pathway, precisely control the interface microstructure, reduce the ion interface migration barrier and charge transfer impedance, and optimize reaction kinetics at the atomic scale. The phosphorus-based composite anode material of this invention has good versatility and can be effectively adapted to lithium-ion, sodium-ion, and potassium-ion alkali metal secondary battery systems.
[0041] In some implementation schemes, an alkali metal fast ion conductor additive phase can be directly added to the phosphorus host material and the carbon conductive phase to obtain a phosphorus-based composite anode material. This direct addition method eliminates the in-situ reaction step, simplifies the process, and allows for precise control of the alkali metal fast ion conductor additive phase content.
[0042] In some embodiments, when the alkali metal is lithium, the alkali metal fast ion conductor additive phase includes at least one of Li₂S, Li₂Se, Li₂Te, Li₃N, LiI, LiBr, LiCl, and LiF; when the alkali metal is sodium, the alkali metal fast ion conductor additive phase includes at least one of Na₂S, Na₂Se, Na₂Te, Na₃N, NaI, NaBr, NaCl, and NaF; when the alkali metal is potassium, the alkali metal fast ion conductor additive phase includes at least one of K₂S, K₂Se, K₂Te, K₃N, KI, KBr, KCl, and KF.
[0043] In some embodiments, the alkali metal fast ion conductor additive phase is distributed in the phosphorus-based composite anode material in the form of a dispersed phase, and the alkali metal fast ion conductor additive phase is at least partially in a nanocrystalline and / or amorphous state.
[0044] In some implementations, the phosphorus host material includes at least one of pretreated or untreated red phosphorus, black phosphorus, and purple phosphorus, existing in at least one of amorphous phosphorus and microcrystalline phosphorus. Pretreatment includes at least one of ball milling, heat treatment, exfoliation, and chemical modification. Red phosphorus, black phosphorus, and purple phosphorus all possess high theoretical specific capacity, ensuring a high energy density substrate for phosphorus-based composite anode materials. Pretreatment helps increase the surface activity of the phosphorus host material, facilitating its combination with alkali metal fast ion conductor additive phases and carbon conductive phases, further optimizing ion and electron conduction efficiency.
[0045] In some implementations, the phosphorus host material includes at least one of red phosphorus, black phosphorus, and purple phosphorus, obtained by stripping pretreatment to obtain nano-sized phosphorus.
[0046] In some embodiments, the pretreatment is preferably carried out under an inert atmosphere, preferably argon. When the pretreatment includes ball milling, the ball milling speed can be 200-900 rpm, and the ball milling time can be 0.5-48 h. When the pretreatment includes heat treatment, the heat treatment temperature can be 80-300 °C, and the heat treatment pressure can be atmospheric pressure, negative pressure, or pressurized conditions.
[0047] In some implementation schemes, the carbon conductive phase includes at least one of natural graphite, artificial graphite, hard carbon, soft carbon, conductive carbon black, carbon nanotubes, graphene, and carbon fiber. These carbon conductive phases can synergistically construct a continuous conductive network, further improving the electronic conductivity of the phosphorus-based composite anode material and reducing the degree of polarization.
[0048] In some implementation schemes, the mass fraction of the phosphorus host material is 30%-98%, the mass fraction of the carbon conductive phase is 1%-60%, and the mass fraction of the alkali metal fast ion conductor additive phase is 0.1%-30%. This arrangement facilitates the synergistic matching of the functions of the phosphorus host material, the carbon conductive phase, and the alkali metal fast ion conductor additive phase, ensuring the overall high specific capacity of the phosphorus-based composite anode material, while simultaneously constructing a continuous conductive pathway, building a fast ion transport channel, and optimizing interfacial reaction kinetics.
[0049] According to another aspect of the present invention, a method for preparing the above-mentioned phosphorus-based composite anode material is provided, comprising: combining a phosphorus host material with an additive phase precursor to obtain a first composite material; combining the first composite material with a carbon conductive phase to obtain a second composite material; and subjecting the second composite material to a pre-alkali metallization treatment with an alkali metal under a protective gas, so that the alkali metal reacts with the additive phase precursor to form an alkali metal fast ion conductor additive phase, thereby obtaining a phosphorus-based composite anode material comprising a phosphorus host material, a carbon conductive phase, and an alkali metal fast ion conductor additive phase.
[0050] According to an embodiment of the present invention, the phosphorus host material is first composited with an additive phase precursor to ensure that the additive phase precursor is uniformly dispersed in the phosphorus host material. Then, it is composited with a carbon conductive phase to construct an electron conduction network. Finally, through pre-alkali metallization treatment, the alkali metal undergoes an atomic-level in-situ reaction with the additive phase precursor to generate an alkali metal fast ion conductor additive phase. This achieves fine dispersion of the alkali metal fast ion conductor additive phase, effectively suppressing aggregation and local enrichment. The atomically constructed ion transport pathway exhibits good continuity and fewer interface defects, effectively reducing the ion migration kinetic energy barrier. This optimizes the interface charge transfer characteristics at the microscale, improving the material's rate performance and cycle stability.
[0051] In some implementations, the phosphorus host material is compounded with the additive phase precursor by at least one of mechanical ball milling and heat treatment.
[0052] In some embodiments, the first composite material is compounded with the carbon conductive phase by mechanical ball milling. Preferably, this is carried out under an inert atmosphere, such as argon, with a milling speed of 200-900 rpm and a milling time of 0.5-48 h.
[0053] In some implementations, the alkali metal is lithium, sodium, or potassium, and the pre-alkali metallization treatment is correspondingly a pre-lithiation treatment, a pre-sodiumization treatment, or a pre-potassiumization treatment.
[0054] In some implementations, the pre-alkali metallization treatment includes either chemical pre-alkali metallization or electrochemical pre-alkali metallization. Chemical pre-alkali metallization is simple to operate; electrochemical pre-alkali metallization allows for controllable alkali metal intercalation and uniform interfacial reaction.
[0055] In some implementations, the electrochemical pre-alkali metallization treatment includes: pressure-assisted electrochemical pre-alkali metallization treatment, with a pressure of 1-50 MPa, a temperature of 25-250 °C, and a potential of 0.1-1.5 V. This setup is beneficial for improving the uniformity of pre-alkali metallization, strengthening interfacial bonding, reducing irreversible capacity, and improving cycle performance.
[0056] In some implementation schemes, taking lithium (Li) as the alkali metal and selenium (Se) as the precursor of the added phase as an example, the alkali metal fast ion conductor added phase formed is a Li-Se configuration. It is a dynamic local coordination center formed in situ by Se sites in the lattice during the pressure-assisted electrochemical pre-lithiation process and continues to exist in the subsequent phosphorus (P) alloying process.
[0057] Specifically, Se is inserted into the P lattice in a substituted form, initially existing as Se-P coordination. During pressure-assisted electrochemical pre-lithiation, the local environment shifts from Se-P dominance to Li-Se coordination. The first Li-Se coordination shell remains at approximately 2.3 Å and persists throughout the subsequent P alloying process. With increasing SOC, the Li-Se-related first shell peak gradually intensifies, indicating an increase in Li enrichment around Se. This dynamic Li-Se center continuously improves the reaction kinetics by locally attracting Li, promoting Li enrichment, and lowering the energy barrier of the P alloying reaction.
[0058] According to another embodiment of the present invention, a method for preparing the above-mentioned phosphorus-based composite anode material is also provided, comprising: combining a phosphorus host material with an alkali metal fast ion conductor additive phase and a carbon conductive phase to obtain a phosphorus-based composite anode material.
[0059] According to an embodiment of the present invention, a one-step co-composite process can be used to achieve uniform mixing and dispersion of phosphorus host material, alkali metal fast ion conductor additive phase and carbon conductive phase, simplifying the preparation process. At the same time, the three components work synergistically to effectively reduce electrode impedance and optimize reaction kinetics.
[0060] According to another aspect of the present invention, an alkali metal ion battery anode is provided, comprising the above-mentioned phosphorus-based composite anode material, a conductive agent, a binder, and a current collector.
[0061] According to embodiments of the present invention, a complete negative electrode system comprising the above-mentioned phosphorus-based composite negative electrode material, a conductive agent, a binder, and a current collector is constructed. Using the phosphorus-based composite negative electrode material of the present invention as the active host, the components are synergistically matched to improve the integrity of the electrode structure, interface stability, and reaction kinetics, enabling the negative electrode to possess high energy density, excellent rate fast charging capability, and low-temperature (-50-0℃) cycling performance.
[0062] In some embodiments, the preparation method of the above-mentioned alkali metal ion battery anode can be to mix a phosphorus-based composite anode material with a conductive agent and a binder, and then coat or lay it on a current collector to obtain an alkali metal ion battery anode. The conductive agent can be conductive carbon black, the binder can be polyvinylidene fluoride (PVDF), and the current collector can be copper foil. For example, the preparation method can be to mix the phosphorus-based composite anode material with a solution of conductive carbon black and polyvinylidene fluoride (PVDF), coat it on a copper foil, and dry it to obtain the alkali metal ion battery anode.
[0063] According to another embodiment of the present invention, the application of the above-mentioned phosphorus-based composite anode material or the above-mentioned alkali metal ion battery anode in an alkali metal secondary battery is provided.
[0064] According to embodiments of the present invention, the phosphorus-based composite anode material or alkali metal ion battery anode of the present invention can be adapted to low-temperature charge and discharge (temperature -50-0℃), high-rate charge and discharge (current density of 4-10C, 1C=1A / g) or fast charging (charged to more than 80% of the theoretical discharge specific capacity within 10 minutes) of alkali metal secondary batteries.
[0065] In some implementations, alkali metal secondary batteries include lithium-ion batteries, sodium-ion batteries, or potassium-ion batteries.
[0066] In some embodiments, alkali metal secondary batteries include liquid electrolyte batteries, semi-solid batteries, or all-solid batteries. The phosphorus-based composite anode material or alkali metal ion battery anode of the present invention can be adapted to different electrolyte conduction environments, thus broadening the range of applicable battery types.
[0067] The technical solution of the present invention will be further illustrated below through specific embodiments. It should be noted that the specific embodiments described below are merely illustrative examples, and the scope of protection of the present invention is not limited thereto.
[0068] Examples 1-6
[0069] Black phosphorus and the additive phase precursors from Examples 1-6 were separately placed in a mortar and pestle mill and ground using an agate mortar and pestle at 100 rpm for 20 min. The resulting material was placed in a 10 mL sample bottle, filled with argon gas, sealed, and then placed in a 10 mL hydrothermal reactor. The mixture was then pressurized (152 kPa) and heated (221 °C) under an argon atmosphere for 10 h to obtain a physically mixed sample. Subsequently, the physically mixed sample was ball-milled at 800 rpm for 18 h under an argon atmosphere using a vibrating ball mill to obtain the first composite material. The mass ratio of the additive phase precursors to black phosphorus in Examples 1-6 and the naming of the first composite material are shown in Table 1.
[0070] Table 1. Mass ratio of added phase precursor to black phosphorus in Examples 1-6 and naming of the first composite material.
[0071]
[0072] Figures 1-6 The images shown are scanning electron microscope (SEM) images and elemental distribution diagrams of the first composite materials in Examples 1-6, respectively.
[0073] like Figures 1-6 As shown, the added phase precursor has been successfully introduced into the phosphorus host material, but it still exhibits a certain degree of local aggregation at the micron scale.
[0074] Examples 7-12
[0075] The first composite material from Examples 1-6 was mixed with artificial graphite (AML350 or AML400) powder at a mass ratio of 1:1 and ball-milled at 800 rpm for 18 hours under an argon atmosphere to obtain the second composite material. Subsequently, the second composite material was pressed into a sheet electrode as the working electrode in an argon-atmosphere glove box and assembled with a lithium metal sheet as the counter electrode and a separator to form an electrochemical system. Pressure-assisted electrochemical pre-lithiation treatment was then performed at a pressure of 10 MPa and a temperature of 60°C, with the sheet electrode positioned relative to Li... + The lithium was discharged to a potential of 0.5V and held at a constant potential for 2 hours, allowing the lithium to react with the precursor to form an alkali metal fast ion conductor additive phase, resulting in a phosphorus-based composite anode material comprising a phosphorus host material, a carbon conductive phase, and an alkali metal fast ion conductor additive phase. The mass ratio of the first composite material to artificial graphite in Examples 7-12 and the naming of the phosphorus-based composite anode materials are shown in Table 2.
[0076] Table 2. Mass ratio of the first composite material to artificial graphite and naming of the phosphorus-based composite anode material in Examples 7-12
[0077]
[0078] Figures 7-12 SEM images and elemental distribution diagrams of the phosphorus-based composite anode materials of Examples 7-12 are shown.
[0079] like Figures 7-12 As shown, the distribution uniformity of the alkali metal fast ion conductor additive phase at the micrometer scale is significantly improved after pre-lithiation treatment.
[0080] Figure 13 The image shows the Se K-edge X-ray absorption near-edge structure spectrum of the phosphorus-based composite anode material and the corresponding added phase precursor and the first composite material in Example 7.
[0081] like Figure 13 As shown, the white line peaks of the added phase precursor Se and the first composite material Se@P are located at approximately 12659.5 eV and 12660.0 eV, respectively. After pre-lithiation treatment, the peak position of the phosphorus-based composite anode material Li-Se@PG shifts positively to approximately 12663.5 eV and changes from a sharp peak to a broadened, asymmetric peak. The chemical shift and peak broadening of approximately 4.0 eV indicate that the initial Se-Se coordination is disrupted, forming the added phase Li2Se, an alkali metal fast ion conductor with a Li-Se configuration.
[0082] Examples 13-16
[0083] Red phosphorus raw material was added to carbon disulfide (CS2) and dispersed in a 50 mL flask. The dispersion was then continuously sonicated for 12 hours in an ice-water bath at 500 W to avoid affecting the material structure due to temperature rise during sonication. After sonication, the resulting dispersion was freeze-dried under vacuum and thoroughly washed to remove residual solvent, ultimately yielding nano-phosphorus (nano-P).
[0084] Nano-sized phosphorus was added to a ball mill jar along with lithium salt (used as an alkali metal fast ion conductor additive phase in Examples 13-16) and artificial graphite (AML400) in a predetermined ratio, and then wet-milled under an argon atmosphere. N-methylpyrrolidone (NMP) was used as the dispersion medium during milling, with a total material mass of 300 mg and 8 milling beads added. The milling speed was 800 rpm, and the milling time was 18 h to ensure sufficient contact and uniform compounding of the components. After milling, the resulting slurry was centrifuged under an argon atmosphere, and then vacuum-filtered and dried to remove NMP, yielding a phosphorus-based composite anode material. The raw material feed ratios and naming of the phosphorus-based composite anode materials in Examples 13-16 are shown in Table 3.
[0085] Table 3. Raw material feed ratios and naming of phosphorus-based composite anode materials in Examples 13-16
[0086]
[0087] Application Examples 1-5
[0088] Application Examples 1-5 use the phosphorus-based composite anode materials of Examples 9-13 as anode active materials for lithium-ion batteries to prepare anode sheets, assemble lithium-ion coin cells, and conduct tests.
[0089] 1. Electrode preparation
[0090] Take 80 mg of the phosphorus-based composite anode material powder from Examples 9-13, and 10 mg of conductive carbon black, grind them evenly, then add 125 mg of 8% (w / w) polyvinylidene fluoride (PVDF) solution, and continue grinding to prepare a uniform slurry. Coat the resulting slurry evenly onto a copper foil and vacuum dry at 50°C for 12 hours to obtain the anode sheet. Based on the total mass of the dried anode active material layer, the mass fractions of the phosphorus-based composite anode material, conductive carbon black, and PVDF are 80%, 10%, and 10%, respectively. The copper foil is not included in the total mass of the anode active material layer.
[0091] 2. Lithium-ion button cell assembly
[0092] The assembled battery is a CR2032 lithium-ion coin cell, with a lithium metal sheet as the counter electrode, a 1 mol / L lithium hexafluorophosphate (LiPF6) solution dissolved in ethylene fluorocarbonate / diethyl carbonate (FEC:DEC=1:1, volume ratio) as the electrolyte, and a polypropylene separator. The charge and discharge voltage range is 0.001-2V.
[0093] Comparative Example 1
[0094] 1. Material preparation
[0095] Black phosphorus and artificial graphite were mixed at a mass ratio of 1:1. A total mass of 300 mg of the mixture was taken and 8 grinding balls were added. The grinding jar was sealed and argon gas was introduced as a protective atmosphere. The mixture was ball-milled at 800 rpm for 18 h to obtain Comparative Example 1, named PG.
[0096] 2. Electrode preparation
[0097] Take 80 mg of the powder obtained from Comparative Example 1, and 5 mg of conductive carbon black. Grind them evenly and add them to an 8 wt% polyvinylidene fluoride (PVDF) solution. Then add 5 mg of single-walled carbon nanotubes and continue grinding to prepare a uniform slurry. Coat the obtained slurry evenly on a copper foil and vacuum dry it at 50 °C for 12 h to obtain the negative electrode sheet.
[0098] 3. Lithium-ion button cell assembly
[0099] The assembled battery is a CR2032 lithium-ion coin cell, with a lithium metal sheet as the counter electrode, a 1 mol / L lithium hexafluorophosphate (LiPF6) solution dissolved in ethylene fluorocarbonate / diethyl carbonate (FEC:DEC=1:1, volume ratio) as the electrolyte, and a polypropylene separator. The charge and discharge voltage range is 0.001-2V.
[0100] 4. Lithium-ion button cell assembly
[0101] The assembled battery is a CR2032 type lithium-ion button cell. After formation using a half-cell assembly method, lithium nickel cobalt manganese oxide is used as the positive electrode. The electrolyte is a propylene carbonate / ethyl acetate (PC:EA=3:7, volume ratio) solution containing 1 mol / L lithium hexafluorophosphate (LiPF6) dissolved in 10% fluoroethylene carbonate (FEC) additive. A polyethylene separator is used, and the charge / discharge voltage range is 1.5-3.8V.
[0102] 5. Assembly of lithium-ion button cells
[0103] The assembled battery is a CR2032 type lithium-ion coin cell symmetrical battery, with two identical negative electrode sheets as symmetrical electrodes, a 1 mol / L lithium hexafluorophosphate (LiPF6) solution dissolved in ethylene carbonate / diethyl carbonate (EC:DEC=1:1, volume ratio) as electrolyte, and a polypropylene separator.
[0104] Corresponding to Use Case 1 - Application Example 5, a constant current charge-discharge test was performed on the lithium-ion coin cell half-cell of Comparative Example 1. The test current density was 0.1 A / g, and the test results are as follows: Figures 14-19 As shown.
[0105] Figures 14-19 The figures are the charge-discharge curves of lithium-ion button cells for Application Examples 1-5 and Comparative Example 1, respectively.
[0106] like Figures 14-19 As shown in Table 4, compared to Comparative Example 1, which did not introduce an alkali metal fast ion conductor additive phase, Examples 9-13 all exhibited higher first-cycle (i.e., first-cycle) coulombic efficiency. The first-cycle reversible specific capacity of Comparative Example 1 was 1104 mAh / g, and the first-cycle coulombic efficiency was 69.4%; the first-cycle reversible specific capacity of Examples 9-13 was 944-1266 mAh / g, and the first-cycle coulombic efficiency increased to 80.8%-82.2%, an improvement of 11.4-12.8% compared to Comparative Example 1.
[0107] In Comparative Example 1, the proportion of phosphorus active material is relatively high, thus it still exhibits a high first-cycle reversible specific capacity, but its first-cycle coulombic efficiency is low, indicating that the first-cycle irreversible reaction is more severe. Examples 9-12, through pre-lithiation treatment to form a lithium-containing alkali metal fast ion conductor additive phase, can compensate for the first-cycle irreversible lithium loss and promote uniform phosphorus alloying. Example 13, by directly adding the alkali metal fast ion conductor additive phase LiCl, can also improve local ion transport and interfacial reactions, increasing the first-cycle coulombic efficiency to 82.2%. The composition, content, and introduction method of the alkali metal fast ion conductor additive phases in Examples 9-13 differ, therefore their first-cycle reversible specific capacities vary.
[0108] The above results demonstrate that introducing an alkali metal fast ion conductor additive phase into the phosphorus-based composite anode material can reduce irreversible specific capacity loss during the first-cycle reaction, improve the first-cycle coulombic efficiency, and allow the electrochemical activity of the phosphorus-based composite anode material to be fully utilized. This is because the alkali metal fast ion conductor additive phase constructs a localized structure within the electrode that facilitates rapid migration and uniform reaction of alkali metal ions, promoting a more complete and controllable phosphorus alloying reaction, thereby improving the first-cycle coulombic efficiency while maintaining a high specific capacity. These results prove that the alkali metal fast ion conductor additive phase modification strategy of this invention is beneficial for improving the first-cycle coulombic efficiency and activity utilization rate of the phosphorus-based composite anode material.
[0109] Table 4. First-cycle reversible specific capacity and first-cycle coulombic efficiency of Examples 9-13 and Comparative Example 1
[0110]
[0111] Application Example 6
[0112] Application Example 6 uses the following phosphorus-based composite anode material as the anode active material for sodium-ion batteries to prepare anode sheets, assemble sodium-ion coin cells, and conduct tests.
[0113] 1. Material preparation
[0114] The only difference from Example 7 is that a sodium metal sheet is used instead of a lithium metal sheet to obtain the phosphorus-based composite anode material Na-Se@PG.
[0115] 2. Electrode preparation
[0116] Take 80 mg of the above-mentioned phosphorus-based composite negative electrode material Na-Se@PG powder, and 10 mg of conductive carbon black. Grind them evenly and then add them to a 3 wt% sodium carboxymethyl cellulose (CMC) solution for further grinding. Then add 5 mg of styrene-butadiene rubber (SBR) with a solid content of 2% to prepare a uniform slurry. Coat the obtained slurry evenly on copper foil and vacuum dry it at 50°C for 12 h to obtain the negative electrode sheet.
[0117] 3. Sodium-ion button cell assembly
[0118] The assembled battery is a CR2032 sodium-ion button cell, with sodium vanadium phosphate as the positive electrode and 1 mol / L sodium hexafluorophosphate (NaPF6) dissolved in a propylene carbonate / diethyl carbonate (PC:DEC=1:1, volume ratio) solution containing 10% fluoroethylene carbonate (FEC) additive as the electrolyte. A glass fiber separator is used, and the charge-discharge voltage range is 2-3.8V.
[0119] The sodium-ion coin cell corresponding to Case 6 underwent rate performance testing. During the test, the battery was subjected to constant current charge-discharge tests sequentially at rates of 0.1C, 1C, 4C, 6C, 8C, and 10C, with five consecutive cycles at each rate to examine capacity retention and reaction kinetics under different current densities. The test results are as follows: Figure 20 As shown.
[0120] Figure 20 The charge-discharge curves and state of charge (SOC)-time curves of the sodium-ion coin cell in Example 6 at different charge-discharge rates are shown.
[0121] like Figure 20As shown, a is the charge-discharge curve, and b is the SOC-time curve. The results indicate that the battery in Application Example 5 exhibits good rate performance, maintaining a high reversible specific capacity in the high-rate region (4C-10C), demonstrating excellent rate response. At a 10C current density, the battery can achieve rapid charging from 0 to 80% SOC within 5 minutes. These results demonstrate that introducing an alkali metal fast-ion conductor additive phase can construct local transport channels within the phosphorus-based composite anode material that facilitate the rapid migration of alkali metal ions, reducing polarization during high-rate charge-discharge processes, promoting phosphorus alloying / dealloying reactions, and thus improving the rate performance of the phosphorus-based composite anode material.
[0122] Application Example 7
[0123] Application Example 7 uses the phosphorus-based composite anode material of Example 7 as the anode active material for lithium-ion batteries to prepare anode sheets, assemble lithium-ion coin cells, and conduct low-temperature tests.
[0124] 1. Electrode preparation
[0125] Take 80 mg of the phosphorus-based composite negative electrode material powder from Example 7, and 5 mg of conductive carbon black. Grind them evenly and add them to an 8 wt% polyvinylidene fluoride (PVDF) solution. Then add 5 mg of single-walled carbon nanotubes and continue grinding to prepare a uniform slurry. Coat the obtained slurry evenly on a copper foil and vacuum dry it at 50°C for 12 h to obtain the negative electrode sheet.
[0126] 2. Lithium-ion button cell assembly
[0127] The assembled battery is a CR2032 type lithium-ion button cell. After formation using a half-cell assembly method, lithium nickel cobalt manganese oxide is used as the positive electrode. The electrolyte is a propylene carbonate / ethyl acetate (PC:EA=3:7, volume ratio) solution containing 1 mol / L lithium hexafluorophosphate (LiPF6) dissolved in 10% fluoroethylene carbonate (FEC) additive. A polyethylene separator is used, and the charge / discharge voltage range is 1.5-3.8V.
[0128] Corresponding to Case 7, the lithium-ion coin cell full cell of Comparative Example 1 underwent cycle performance testing at -10℃. The test used a 2C charge / 0.2C discharge rate to examine the cycle stability of the negative electrode material under low temperature and asymmetric rate conditions. The test results are as follows: Figure 21 As shown.
[0129] Figure 21 The graph shows the areal capacity and coulombic efficiency of the lithium-ion coin cells of Application Example 7 and Comparative Example 1 as a function of the number of cycles at a temperature of -10°C.
[0130] like Figure 21As shown, Comparative Example 1 exhibits a significant decrease in discharge surface capacity with increasing cycle count during low-temperature cycling, resulting in poor cycle stability. In contrast, Application Example 7 demonstrates better cycle stability under the same test conditions. Its discharge surface capacity decreases slowly during long-term cycling, and its coulombic efficiency remains at a high level. It can operate stably for over 800 cycles at -10°C.
[0131] Furthermore, the lithium-ion button cell full battery corresponding to Case 7 and Comparative Example 1 was subjected to charge-discharge tests at -20°C and 0.1C.
[0132] Figure 22 The charge-discharge curves of the lithium-ion coin cells used in Application Example 7 and Comparative Example 1 at a temperature of -20°C are shown.
[0133] like Figure 22 As shown, under lower temperature conditions, Comparative Example 1 could hardly exert its effective specific capacity, and its charge-discharge curve exhibited obvious polarization characteristics. In contrast, Application Example 7 was able to maintain a more complete charge-discharge curve morphology under the same conditions, and its reversible specific capacity reached more than 70% of the room temperature reversible specific capacity, showing better low-temperature electrochemical activity.
[0134] Application Examples 8-11
[0135] Application Examples 8-11 use the phosphorus-based composite anode materials of Examples 13-16 as anode active materials for lithium-ion batteries to prepare anode sheets, assemble lithium-ion coin cells, and conduct tests.
[0136] 1. Electrode preparation
[0137] Take 80 mg of the phosphorus-based composite negative electrode material powder from Examples 13-16, and 10 mg of conductive carbon black respectively. Grind them evenly and then add them to an 8 wt% polyvinylidene fluoride (PVDF) solution for further grinding to prepare a uniform slurry. Coat the obtained slurry evenly on a copper foil and vacuum dry it at 50°C for 12 h to obtain the negative electrode sheet.
[0138] 2. Assembly of lithium-ion button cells
[0139] The assembled battery is a CR2032 type lithium-ion coin cell symmetrical battery, with two identical negative electrode sheets as symmetrical electrodes, a 1 mol / L lithium hexafluorophosphate (LiPF6) solution dissolved in ethylene carbonate / diethyl carbonate (EC:DEC=1:1, volume ratio) as electrolyte, and a polypropylene separator.
[0140] Corresponding to Case Study 8 - Application Example 11, the lithium-ion coin cell symmetric battery of Comparative Example 1 underwent a linear scan voltammetry test on an electrochemical workstation. The voltage bias was 50 mV (relative to the open-circuit voltage), and the scan rate was 10 mV / s. The test results are shown in Table 5. The exchange current density of Comparative Example 1 was 0.33 mA / cm². 2 In contrast, the exchange current densities of Examples 13-16, which introduced alkali metal fast ion conductor additive phases, were increased to 0.85, 0.55, 0.58, and 0.45 mA / cm², respectively. 2 The values were all higher than those in Comparative Example 1. This result indicates that the addition of an alkali metal fast ion conductor phase can improve the interfacial reactivity of phosphorus-based composite anode materials, reduce charge transfer polarization, and thus promote the alloying reaction kinetics of phosphorus.
[0141] Table 5. Exchange current density of Examples 13-16 and Comparative Example 1
[0142]
[0143] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above descriptions are merely specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A phosphorus-based composite anode material, comprising a phosphorus host material, a carbon conductive phase, and an alkali metal fast ion conductor additive phase; The alkali metal fast ion conductor additive phase includes at least one of alkali metal sulfides, alkali metal selenides, alkali metal tellurides, alkali metal nitrides, and alkali metal halides.
2. The phosphorus-based composite anode material according to claim 1, wherein, The alkali metal fast ion conductor additive phase is obtained by pre-alkali metallization treatment of the additive phase precursor and alkali metal under a protective atmosphere, or by directly adding the alkali metal fast ion conductor additive phase. The added phase precursor includes at least one of elemental sulfur, elemental selenium, elemental tellurium, elemental iodine, and elemental bromine.
3. The phosphorus-based composite anode material according to claim 1 or 2, wherein, The alkali metal includes lithium, sodium, or potassium.
4. The phosphorus-based composite anode material according to claim 1, wherein, In the phosphorus-based composite anode material, the mass fraction of the phosphorus host material is 30%-98%, the mass fraction of the carbon conductive phase is 1%-60%, and the mass fraction of the alkali metal fast ion conductor additive phase is 0.1%-30%.
5. The phosphorus-based composite anode material according to claim 1, wherein, The phosphorus-based material includes at least one of pretreated or untreated red phosphorus, black phosphorus, and purple phosphorus, and the pretreatment includes at least one of ball milling, heat treatment, stripping, and chemical modification. The carbon conductive phase includes at least one of natural graphite, artificial graphite, hard carbon, soft carbon, conductive carbon black, carbon nanotubes, graphene, and carbon fiber.
6. A method for preparing a phosphorus-based composite anode material as described in any one of claims 1-5, comprising: The phosphorus host material was combined with the additive phase precursor to obtain the first composite material; The first composite material is combined with a carbon conductive phase to obtain a second composite material; The second composite material is subjected to pre-alkali metallization treatment with an alkali metal under a protective gas atmosphere, causing the alkali metal to react with the additive phase precursor to form an alkali metal fast ion conductor additive phase, resulting in a phosphorus-based composite anode material comprising the phosphorus host material, a carbon conductive phase, and the alkali metal fast ion conductor additive phase; or Phosphorus-based composite anode materials are obtained by combining phosphorus-based host material with alkali metal fast ion conductor additive phase and carbon conductive phase.
7. The preparation method according to claim 6, wherein, The pre-alkali metallization treatment includes chemical pre-alkali metallization treatment or electrochemical pre-alkali metallization treatment; Preferably, the electrochemical pre-alkali metallization treatment includes pressure-assisted electrochemical pre-alkali metallization treatment; The pressure-assisted electrochemical pre-alkali metallization treatment is 1-50 MPa, the temperature is 25-250℃, and the potential is 0.1-1.5V.
8. An alkali metal ion battery anode, comprising the phosphorus-based composite anode material, conductive agent, binder, and current collector as described in any one of claims 1-5.
9. The application of a phosphorus-based composite anode material as described in any one of claims 1-5 or an alkali metal ion battery anode as described in claim 8 in an alkali metal secondary battery.
10. The application according to claim 9, wherein, The alkali metal secondary battery includes a liquid electrolyte battery, a semi-solid battery, or an all-solid battery.
